Keanekaragaman katak dan kodok (Amphibia: Anura) di Suaka Margasatwa Paliyan, Gunungkidul, Yogyakarta - Yudha, Donan Satria; Eprilurahman, Rury; Asti, Hastin Ambar; Azhar, Herofi; Wisudhaningrum, Nurrochmah; Lestari, Puji; Markhamah, Siti; Sujadi, Imam (Jurnal Biologi Udayana; Vol 23 No 2 (2019): JURNAL BIOLOGI UDAYANA, 2019)
Frogs and toads commonly found by human. Frogs and toads could become a bio-indicator of an environment. Paliyan Wildlife Sanctuary is a forest area which posses several animal to protect and it’s located in Gunungkidul Regency, Province of DIY. The diversity of frogs and toads in this wildlife sanctuary is not yet recorded and published. The aim of this research is to understand the diversity of frogs and toads in the area of Paliyan Wildlife Sanctuary. The results there were 9 species of frogs and toads, i.e., Duttaphrynus melanostictus, Ingerophrynus biporcatus, Fejervarya limnocharis, Kaloula baleata, Occidozyga lima, Occidozyga sumatrana, Microhyla orientalis, Microhyla palmipes and Polypedates leucomystax. The diversity of frogs and toads in the wildlife sanctuary is moderate according to the Shannon-Wiener Index with value: 1,43. Area of Paliyan Wildlife Sanctuary is a suitable habitat for frogs and toads due to its location with dense forest, bushes, rivers, lakes and pools as well as least human activities.